Effective Government Accounting - Premchand, A. (International Monetary Fund, 1995)
This book, by A. Premchand, seeks to bridge fiscal economics and government accounting. It examines historical developments, ingredients of existing systems, features of accounting standards, and other issues that governments must address to perform their tasks economically and efficiently. Readers gain insights into institutional linkages and the role of electronic technology. Arguing that government accounting systems are too important to be left to accountants alone, the book presents an interdisciplinary approach that goes beyond adapting commercial accounting formats to governments.